ISLAMIC FINANCIAL INCLUSION AND ECONOMIC GROWTH IN OIC COUNTRIES: PANEL QUANTILE REGRESSION ANALYSIS - Ameziane, Massinissa (Bank Indonesia, 2024)
This study examines how Islamic financial inclusion contributes to economic growth across different quantiles within the OIC countries. Sarma’s method is used to construct a novel index of Islamic financial inclusion (IIFI) and a quantile regression with fixed effects approach is applied to data spanning the period 2015 to 2020 from 25 OIC countries. The findings reveal that Islamic financial inclusion contributes positively to economic growth in the OIC countries across different segments of the GDP per capita with the impact being consistent across all segments. By expanding the network of Islamic banks and enhancing the technological infrastructure for financial access, policymakers can harness the transformative potential of Islamic finance to promote sustainable economic growth and development in the OIC countries.